North Sumatran Malay Folktales: Its Structure, Social Function and Meaning: (Cerita Rakyat Melayu Sumatera Utara: Struktur, Fungsi Sosial, dan Maknanya) (Malay Literature, 2015)
This study is a descriptive-qualitative analysis that uses the techniques of observation, interviews and written documents. The Systemic Functional Linguistic (SFL) approach based on the principle of semiotics is used in this study. The data analysis consists of folktales found in North Sumatra, that is, "Batu Belah Batu Betangkup", "Putri Kuau" and "Sri Putih Cermin". By using the SFL approach this study describes the structure, social function, and meaning of North Sumatran Malay folktales. From the analysis it is found that the structure, function and meaning of all the three NSM folktales are similar. The material and verbal processes found in the texts of the folktales depict life in the palace and the everyday life of North Sumatran Malay society in the past as well as in the present. North Sumatran Malay texts are the representation of culture and meaning in which the value of of North Sumatran Malay society are inherent.Keywords: folklore, "Batu Belah Batu Betangkup", "Putri Kuau", "Sri Putih Cermin", systemic functional linguistics, North Sumatran Malay values